Communicate the Risk of Sars-Cov-2: Televised Reports from the Chilean Ministry of Health [Comunicar O Risco Sobre O Sars-Cov-2: Informativos Televisivos Do Ministério Da Saúde Do Chile] [Comunicar el Riesgo Sobre el Sars-Cov-2: Informes Televisados del Ministerio de Salud Chileno] - Rocamora-Villena, V (Pontificia Universidad Catolica de Chile, 2022)
Given the relevance of communication in risk situations to deliver timely information to affected groups, as well as its ability to generate collective meanings, this research aims to analyze the communication deployment of the first stage of the COVID-19 pandemic in Chile from the perspective of risk communication. From a qualitative approach, we conducted a reflective thematic analysis of 88 videos corresponding to the daily coronavirus reports broadcast by Chilean open television, between March 17 and June 12, 2020. Three stages established are: triumphalist, tension, and crisis; in those, we observe a communication focused on promoting the government s management rather than delivering timely information to the population. The use of some discursive resources stands out, such as the metaphor of war or individual responsibility, which generate tension with the need to generate collective meanings to mobilize the population. © 2022 Pontificia Universidad Catolica de Chile. All rights reserved.